Characterization of genomic vitamin D receptor binding sites through chromatin looping and opening. - Sabine Seuter; Antonio Neme; Carsten Carlberg (PLoS ONE, 2014)
The vitamin D receptor (VDR) is a transcription factor that mediates the genomic effects of 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3). Genome-wide there are several thousand binding sites and hundreds of primary 1,25(OH)2D3 target genes, but their functional relation is largely elusive. In this study, we used ChIA-PET data of the transcription factor CTCF in combination with VDR ChIP-seq data, in order to map chromatin domains containing VDR binding sites. In total, we found 1,599 such VDR containing chromatin domains and studied in THP-1 human monocytic leukemia cells four representatives of them. Our combined ChIP-seq and FAIRE-seq time course data showed that each of these four domains contained a master VDR binding site, where an increase of VDR binding pairs with 1,25(OH)2D3-promoted chromatin opening and the presence of a highly significant DR3-type sequence below the peak summit. These sites differed in their relative VDR binding but not in their kinetics, while other loci either had a weaker and delayed VDR association or could not be confirmed at all. All studied chromatin domains contained at least one primary 1,25(OH)2D3 target gene demonstrating a characteristic slope of mRNA increase, while neighboring genes responded delayed, if at all. In conclusion, the observation of ligand-inducible VDR binding and chromatin opening combined with a DR3-type sequence highlighted genome-wide 160 VDR loci that have within their chromatin domain a more than 4-fold increased likelihood to identify a primary 1,25(OH)2D3 target gene than in the vicinity of other genomic VDR binding sites.